2018
DOI: 10.21660/2018.45.7177
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Vegetation Indices for Assessing Mangrove Density Using Sentinel-2 Imagery

Abstract: Vegetation mapping provides important information for understanding ecological condition through calculation of vegetation density. It based on vegetation indices developed through algorithms of a mathematical model within the visible and near-infrared reflectance bands. The index is an estimate of either leaf density per species or vegetation types, respectively. This study aimed to evaluate those indices and find the best algorithm using Sentinel-2 satellite image. Twenty four algorithms of vegetation indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
0
23
0
6
Order By: Relevance
“…Recently, Kamal, Phinn, and Johansen [59] investigated the ability of different optical sensors such as WorldView-2, ALOS AVNIR-2, and Landsat TM for measuring and monitoring mangrove LAI, and showed that ALOS AVNIR-2 data yields the highest accuracy for the LAI estimation of mangrove ecosystems in Karimunjawa Island, Indonesia. More recently, Sentinel-2A data have been employed to retrieve and model mangrove biophysical parameters such as LAI, leaf chlorophyll, and tree density [66,84]. Mangrove canopy heights can also be estimated using the high-resolution stereo-photogrammetry of WorldView-1 data in the Mozambique [58,61].…”
Section: Relationships Between Biophysical Parameters Of Mangroves Anmentioning
confidence: 99%
“…Recently, Kamal, Phinn, and Johansen [59] investigated the ability of different optical sensors such as WorldView-2, ALOS AVNIR-2, and Landsat TM for measuring and monitoring mangrove LAI, and showed that ALOS AVNIR-2 data yields the highest accuracy for the LAI estimation of mangrove ecosystems in Karimunjawa Island, Indonesia. More recently, Sentinel-2A data have been employed to retrieve and model mangrove biophysical parameters such as LAI, leaf chlorophyll, and tree density [66,84]. Mangrove canopy heights can also be estimated using the high-resolution stereo-photogrammetry of WorldView-1 data in the Mozambique [58,61].…”
Section: Relationships Between Biophysical Parameters Of Mangroves Anmentioning
confidence: 99%
“…Chlorophyll Index red-edge ( B7 B5 ) − 1 [32,151,152] Modified Simple Ratio red-edge [32,153,154] Modified Simple Ratio red-edge narrow [32] While less commonly used than other approaches, SMA has successfully assessed burn severity in a few studies [157][158][159]. Quintano et al [158] used a version of SMA called multiple endmember SMA (MESMA) to classify levels of burn severity in three Mediterranean sites located in Spain.…”
Section: Red-edge Spectral Indices Colum Equation Referencesmentioning
confidence: 99%
“…Green radiance (G) = ρG (14) Red radiance (R) = ρR (15) Near -infared radiance (NIR) = ρNIR (16) Green band Plus Red band = ρG + ρR (17) Green band Minus Red band = ρG -ρR (18)…”
Section: Difference Vegetation Index (Dvi) = ρNir -ρR (9)mentioning
confidence: 99%